Correction of Cytokine Profile in Autoimmune Diseases with Embryofetoplacental Complex Cryopreserved Products - Goltsev, Anatoliy; Lutsenko, Olena; Yampolska, Kateryna; Gaevska , Yuliia; Bondarovych , Mykola; Ostankova, Lyudmyla; Sokil , Larisa; Stepaniuk , Lyudmyla; Grisha , Ihor (Problems of Cryobiology and Cryomedicine, 2022)
In this work, we experimentally substantiated the possibility of correcting the cytokine profile to reduce the inflammation in mice with adjuvant arthritis (AA) via combined use of lyophilized human cord blood leukoconcentrate (lHCBL) and cryopreserved human placental extract (cHPE). Adjuvant arthritis was modelled in CBA/H mice. To day 7 after pathology induction, the animals were injected with lHCBL and cHPE singly or in combination. To days 14 and 28 of observation, all the introduced products showed a therapeutic effect. To 28 day of observation, the efficiency of combined use of lHCBL and cHPE was 3.1 and 2.5 times higher vs. the monotherapy (respectively), likely resulting from their synergy in respect to a decrease in arthritis index, TNFα concentration, impact of lHCBL and cHPE on IFNγ and IL-6 levels, correspondingly. Probl Cryobiol Cryomed 2022; 32(2):121–133